2002
DOI: 10.1002/ijc.10715
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of hMLH1, p16INK4a and PTEN in the malignant transformation of endometriosis

Abstract: Endometriosis is a common gynecologic disease, which generally follows a benign course. Notwithstanding, several clinical and histologic studies as well as molecular data show that endometriosis could be a precursor of sporadic endometrioid and clear cell carcinomas at extrauterine loci. Several reports have implicated alterations of the hMLH1 and p16 ink4a (p16) genes, in particular hypermethylation of the promoter region, and of the PTEN gene, principally genetic mutations, in endometrial and ovarian cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 37 publications
2
103
0
6
Order By: Relevance
“…[23][24][25][26][27][28][29] Marker cM 2165T 2165E 914T 914E 247T 247E 18542T 18542E 11MT 11ME 10MT 10ME 8872T 8872E 842T 842E Chrm 3q D3S1614 169.9…”
Section: Discussionunclassified
“…[23][24][25][26][27][28][29] Marker cM 2165T 2165E 914T 914E 247T 247E 18542T 18542E 11MT 11ME 10MT 10ME 8872T 8872E 842T 842E Chrm 3q D3S1614 169.9…”
Section: Discussionunclassified
“…Mutations of PTEN (chromosome 10p23.3) were identified in 20% of both EAC and ovarian endometriosis, suggesting that the PTEN inactivation is an early event in the malignant process of endometriosis (14,16). A separate study identified reduced PTEN protein expression in 15% of endometriosis cases (17). The second hit or carcinogenesis step could be represented by the reduced expression of hMLH1, MSI (17).…”
Section: Loh Involved In Endometrioid Adenocarcinoma (Eac) Of the Ovarymentioning
confidence: 99%
“…A separate study identified reduced PTEN protein expression in 15% of endometriosis cases (Martini et al 2002).…”
Section: Somatic Mutations In Tsgsmentioning
confidence: 99%
“…Hypermethylation of hMLH1 (whose gene product is a component of the DNA mismatch repair pathway), with concurrent absence of hMLH1 protein expression, is noted in 8.6% of endometriotic lesions (Martini et al 2002).…”
Section: Msimentioning
confidence: 99%